Der arme Heinrich - digital: transcriptions - Fernández Riva, Gustavo; Millet, Victor (Universität, 2018)
Hartmann’s von Aue Der arme Heinrich, composed towards the end of the 12th century, is a legendary tale of a man suffering from leprosy who is miraculously healed. This short story (ca. 1500 lines) is today rated as one of the classics, also in academic teaching. Although the number of manuscripts preserved is quite small, the degree of textual variation between them is comparatively high, showing numerous additions, cuts, alterations, and position changes of groups of verses. Find here the TEI transcriptions of the work.
Gesehen am 09.07.2018
Keywords: Forschungsdaten; Datenbank